Deskripsi Motivasi Calon Guru Bahasa Inggris sebagai Bahasa Asing (EFL) Menjadi Guru di Turki - Alp Cengiz (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To describe the motivation of Pre Service English as a Foreign Language (EFL) Teachers to Become Teachers in Turkey, to determine the effect of gender on the motivation of pre-service EFL teachers to become teachers and to find out the influence of the community on a pre-service EFL teacher's decision to become a teacher Methodology: This study was conducted according to a mixed research method. The researcher analyzed the Quantitative data with the SPSS program (Statistical Package for the Social Sciences). In the SPSS program, the researcher created three tables, which are the answer to research questions. The researcher analyzed qualitative data by Computer-assisted qualitative data analysis software (CAQDAS) Quirkos Main Findings: Participants were very excited to become English teachers because they were going to become English teachers; furthermore, during the interview, all participants stated that society influenced their choice of profession. In addition, according to the quantitative data, it appears that the participants were motivated by 9 factors to choose teaching English as a career choice. Novelty/Originality of this study: This study was conducted in one of the state universities in Turkey participant number was limited for this study. Also, this study was conducted in a short time. Due to the limitations, this study’s findings and conclusions can’t be generalized. More detailed and long-lasting studies should be carried out to understand the motivations of pre-service EFL teachers to become teachers.